2019
DOI: 10.4103/ortho.ijortho_119_17
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Component Alignment with a New Extramedullary Femoral Cutting Guide Technique

Abstract: Background:Intramedullary (IM) or extramedullary (EM) mechanical guides are used as alignment tools during total knee arthroplasty (TKA) surgery. The EM guide is less invasive; however, the IM mechanical guide is the preferred option since it has shown superior outcomes in several studies. Picture archive and communication system (PACS) images, if available, are extensively used for preoperative planning and intraoperative guidance. This retrospective study compared TKA outcomes using the conventional IM guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Our study corroborates a growing body of evidence that shows CATKAs are associated with lower odds of postoperative in-hospital complications, but the adoption of this technology does not reflect this. [7][8][9][10][11][12][13][31][32][33][34][35]39,40 In the current study, CATKA represented slightly less than 10% of all TKAs. In another recent study of CATKA trends, modest increases were observed from 2010 to 2017.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our study corroborates a growing body of evidence that shows CATKAs are associated with lower odds of postoperative in-hospital complications, but the adoption of this technology does not reflect this. [7][8][9][10][11][12][13][31][32][33][34][35]39,40 In the current study, CATKA represented slightly less than 10% of all TKAs. In another recent study of CATKA trends, modest increases were observed from 2010 to 2017.…”
Section: Discussionmentioning
confidence: 79%
“…Our results also showed that patients who had CATKAs had fewer pulmonary embolisms, potentially because of the use of computer-assisted alignment guides that lead to fewer emboli. 9 , 10 , 31 , 32 Previous studies have also reported that embolization that occurs during surgical procedures is associated with both intraoperative and postoperative cardiac complications. 8 , 33 - 35 As such, utilization of CATKAs may prevent emboli from occurring, therefore reducing emboli-related cardiac complications.…”
Section: Discussionmentioning
confidence: 99%
“…In all patients, an air tourniquet was applied after elevation of the leg without elastic bandage exsanguination [22]. The patella was replaced with an inset-type component [23]. Periarticular injection of analgesics, including Marcaine 20 mL, morphine 5 mg, ketorolac 30 mg, epinephrine 0.1 mg and transamin 500 mg were given routinely [24].…”
Section: Surgical Technique and Postoperative Nursing Carementioning
confidence: 99%
“…Zahn et al [ 7 ] found that navigation intramedullary and extramedullary instrumentation provided equal precise positioning of the tibial component. Ku et al [ 8 ] performed a retrospective study and identified that extramedullary mechanical guide provides similar postoperative alignment as intramedullary mechanical guide but caused less blood loss.…”
Section: Introductionmentioning
confidence: 99%